Unusual trophic strategies of Hydractinia angusta (Cnidaria, Hydrozoa) from Terra Nova Bay, Antarctica - CERRANO, CARLO; CHIANTORE, MARIACHIARA; BAVESTRELLO, GIORGIO; PUCE S. (2000)
Hydractinia angusta Hartlaub, 1904 has been recorded at Terra Nova Bay (Ross Sea, Antarctica) as epizoic on shells of the Antarctic scallop Adamussium colbecki. The species can exploit di erent trophic re- sources: ®rst, polyps are able to detach and ingest tube feet and pedicellariae from the sea urchins Sterechinus neumayeri, grazing on the scallop shell, and second, they also eat masses of benthic diatoms settled among the hydrorhiza of the colony. The particular relationship observed between the hydroid and one of the most common Antarctic sea urchins may prevent or reduce the damage to A. colbecki shells, otherwise caused by the grazing of sea urchins on the algal ®lm of the upper valve of the scallops. H. angusta is the ®rst known species of hydroid that exploits prey several times its own size and the second that does not ingest entire prey but portions of them. The use of benthic diatoms as a food resource has previously been documented for the sub-Antarctic marine hydroid Silicularia rosea.